Patient experience with cancer care in low- and middle-income Asian countries: a cross-sectional study of patients with advanced cancer - Sushma Bhatnagar; Semra Ozdemir; Chetna Malhotra; Ishwarya Balasubramanian; Hamzah Shatri; Gayatri Palat; Ellie Bostwick Andres; Louisa Poco; Isha Chaudry; Thushari Hapuarachchi; Anjum Khan Joad; Lubna Mariam; et al. (BMJ Global Health, 2025)
Introduction Despite the disproportionate burden of cancer morbidity and mortality in low- and middle-income countries (LMICs), little is known about patients’ care experiences in these settings. This study assesses which aspects of physician communication and care coordination most influence patients’ overall experience with care, and factors associated with patient experience ratings, to inform quality improvement and improve cancer care experiences in LMICs.Methods In a cross-sectional study of 1933 patients with advanced cancer recruited at 10 major public hospitals in seven LMICs in Asia, patients rated their experience with physician communication, care coordination and overall.Results Physician communication mattered most in patients’ assessment of overall experience with care. Patient use of traditional medicine was associated with poorer physician communication ratings (β: −1.38, 95% CI: −2.11 to 0.65), while outpatient care (0.91, 95% CI: 0.24 to 1.57) was associated with higher ratings. Patients who were unsure (−0.77, 95% CI: −1.43 to –0.10) of their cancer stage (relative to aware of late-stage), or indicated financial difficulty (sufficient money to cover their daily needs fairly well (−0.77, 95% CI: −1.50 to –0.04) or poorly (−1.20, 95% CI: −2.30 to –0.09) relative to very well) rated care coordination lower. Patient experience ratings differed by minority group status and cancer severity understanding. Respondents identifying as ethnic minorities who were unsure of their cancer stage rated physician communication significantly higher (1.64, 95% CI: 0.71 to 2.58) than non-minorities aware of their advanced cancer. Non-minorities unsure of their cancer stage rated care coordination significantly lower (−1.00, 95% CI: −1.64 to –0.36) than non-minority patients aware of their cancer stage.Conclusions This study provides new understanding of care priorities among patients with advanced cancer in LMICs. Our findings highlight the importance patients attribute to physician communication and considerations for improving patient-centred communication to support equitable and culturally appropriate care. This study also underscores the need for future work navigating prognostic discussions in LMICs.